1995
DOI: 10.1007/bf01782024
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of some aspects of acute inflammation of guinea-pig lung by intraperitoneal dexamethasone and mifepristone: Demonstration of agonist activity of mifepristone in the guinea-pig

Abstract: We have determined the inhibitory activity of dexamethasone as an inhibitor of histamine-induced plasma protein extravasation (PPE) in guinea-pig lung and skin, and of lipopolysaccharide (LPS)-induced neutrophilia and platelet activating factor (PAF)-induced eosinophilia in guinea-pig lungs. Dexamethasone inhibited PAF-induced eosinophilia in guinea-pig lung (ED50 1.4 mg/kg i.p.). Higher doses of dexamethasone were required to inhibit LPS-induced neutrophilia (ED50 10.8 mg/kg i.p.). However, at doses up to 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
4
9
0
Order By: Relevance
“…The experiments described in the present study confirm, and extend, previous reports which showed that dexamethasone was approximately 10 times more potent as an inhibitor of PAF-induced eosinophilia than of LPSinduced neutrophilia in guinea-pig lung [7]. In these experiments, PAF and LPS were administered to guineapigs as aerosols generated from a nebuliser [7].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The experiments described in the present study confirm, and extend, previous reports which showed that dexamethasone was approximately 10 times more potent as an inhibitor of PAF-induced eosinophilia than of LPSinduced neutrophilia in guinea-pig lung [7]. In these experiments, PAF and LPS were administered to guineapigs as aerosols generated from a nebuliser [7].…”
Section: Discussionsupporting
confidence: 92%
“…In man, glucocorticoid therapy appears to show some selectivity for inhibition of asthmatic inflammation over the other forms of airway inflammation, since clinical studies show that 10 fold greater doses of beclomethasone dipropionate (BDP) are required to produce a significant therapeutic effect in bronchitis when compared to asthma [5, 61. Similarly, recent studies in guinea-pigs have shown that dexamethasone is 10 times more potent as an inhibitor of PAF-induced eosinophilia than of LPSinduced neutrophilia [7]. The experiments described below extend these findings by describing the inhibitory potency of dexamethasone, administered intraperitoneally, on eosinophilia induced by intratracheal administration of PAF and interleukin (IL)-5 and on neutrophilia induced by intracheal administration of LPS, TNFc~ and the chemokines IL-8 and CINC.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Second, glucocorticoids stimulate the expression of MR [21], which could explain how glucocorticoids augment the salt appetite seen in mineralocorticoid-treated rats [22]. Even a partial agonist activity of a GR antagonist [39, 40, 41, 42, 43]may enhance DOCA-induced salt intake [44]. Thus, although previous studies focused on the interaction between mineralocorticoids and AngII, glucocorticoids may also play an important role in increasing MR and AngII in the brain, thereby promoting behavioral interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Control groups receiving chronic saline and the drug treatments were, however, included. Doses of dexamethasone (Whelan et al, 1995;Toward and Broadley, 1999) and rolipram (Danahay and Broadley, 1997) were selected based upon the findings from other studies using similar models of inflammation and those that were without adverse effects. No animal appeared to be in respiratory distress or to exhibit other signs of discomfort during the exposure regimens or during any other part of the protocol described.…”
mentioning
confidence: 99%